Semi-stability for Holomorphic Bundles with Global Sections (Journal of Partial Differential Equations, 2016)
In this paper, we establish a generalized Hitchin-Kobayashi correspondence between the τ-semi-stability and the existence of approximate τ-Hermitian-Einstein structure on holomorphic pair (E,Φ). As an application, we obtain the Bogomolov type inequality for τ-semi-stable holomorphic pair.
Keywords: τ-semi-stable; approximate τ-Hermitian-Einstein structure; holomorphic pair